94.5k views
1 vote
2e - 3(2e + 3) = 3e + 5
What is e?

1 Answer

2 votes


\boxed{e\:=\:-2.}


\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\orange{:}}}}}


2e - 3(2e + 3) = 3e + 5 \\ ⇢2e - 6e - 9 = 3e + 5 \\ ⇢ - 4e - 3e \: = 5 + 9 \\ ⇢ - 7e = 14 \\ ⇢e = (14)/( - 7) \\ ⇢e = - 2


{ \bf{ \underbrace{To\:verify :}}}


2e - 6e - 9 = 3e + 5 \\⇢2 * - 2 - 6 * - 2 - 9 = 3 * - 2 + 5 \\ ⇢ - 4 + 12 - 9 = - 6 + 5 \\ ⇢12 - 13 = - 1 \\ ⇢ - 1 = - 1 \\ ⇢L.H.S.=R. H. S

Hence verified.


\large\mathfrak{{\pmb{\underline{\orange{Happy\:learning }}{\orange{.}}}}}

User Btx
by
6.2k points